Bureaucratic Barrier Mitigation Strategy in Smart City Implementation in Cimahi City - Genis Arivanny Putri Sekarsari (SEAN Institute, 2026)
The implementation of Smart City policies often faces non-technical obstacles in the form of structural rigidity and resistance from the government bureaucratic work culture. This study aims to identify clusters of bureaucratic obstacles in Smart City implementation in Cimahi City and formulate comprehensive mitigation strategies. Using qualitative research methods with a descriptive approach, data were collected through in-depth interviews with key informants from the Cimahi City Communication and Information Technology Office (Diskominfo) and the Regional Development Planning Agency (Bappeda), system observations, and documentation studies of supporting regulations. The results indicate that smart city implementation is hampered by six main factors: sectoral egos that trigger data silos, the clash between rigid structures and digital dynamics, apparatus resistance to change, limited human resource ICT competencies, a reductive mindset toward